2014
DOI: 10.1002/arch.21215
|View full text |Cite
|
Sign up to set email alerts
|

Paralytic Peptide: An Insect Cytokine That Mediates Innate Immunity

Abstract: Host animals combat invading pathogens by activating various immune responses. Modulation of the immune pathways by cytokines is critical for efficient pathogen elimination. Insects and mammals possess common innate immune systems, and individual immune pathways have been intensively studied over the last two decades. Relatively less attention, however, has been focused on the functions of cytokines in insect innate immunity. Here, we summarize our recent findings from studies of the insect cytokine, paralytic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 77 publications
1
7
0
Order By: Relevance
“…We previously reported the activation of innate immunity in silkworm during pathogen invasion and found that a cytokine-like paralytic peptide induced humoral and cellular responses and played an important role in silkworm immunity. Further, we found that the paralytic peptide promoted the engulfment of bacteria and induced nitric oxide (NO) production, that is required for both p38 and MAPK activation (Ishii et al, 2013, 2015a). …”
Section: Advantages Of the Silkworm As An Animal Modelmentioning
confidence: 99%
“…We previously reported the activation of innate immunity in silkworm during pathogen invasion and found that a cytokine-like paralytic peptide induced humoral and cellular responses and played an important role in silkworm immunity. Further, we found that the paralytic peptide promoted the engulfment of bacteria and induced nitric oxide (NO) production, that is required for both p38 and MAPK activation (Ishii et al, 2013, 2015a). …”
Section: Advantages Of the Silkworm As An Animal Modelmentioning
confidence: 99%
“…In insects, pathogens are recognized as “nonself” and further removed by the synergistic action of both humoral and cellular responses [11, 22], and proteins such as defensin, moricin and lectin were reported to participate in the regulation of immune responses [2325]. Evidence suggests that serine proteases may be involved in resistance to pathogenic invasion in insects.…”
Section: Discussionmentioning
confidence: 99%
“…Determining whether or not immunity is activated in humans and other mammals is usually difficult. We found that stimulating innate immunity in silkworms causes muscle contractions (10,11). Activation of cells responsible for innate immunity in silkworms leads to enhancement of immune cells that results in the activation of a cytokine that has the pharmacologic capacity to induce muscle contractions.…”
mentioning
confidence: 95%